Library management in disruptive times skills and knowledge for an uncertain future - O'Connor, Steve (Facet, 2018)
Library Management in Disruptive Times identifies the key skills and attitudes needed by the library leaders of today and tomorrow and delivers a balanced view of the future of the profession. Contributed to by expert professional library leaders and educators from across the globe, this edited collection offers thought-provoking perspectives on the challenge of the current operating environment across a range of library sectors, library professional associations and geographic regions. Each author brings their own particular area of expertise and perspective on to consider the effects of disruptive change in libraries globally
Title from publisher's bibliographic system (viewed on 05 Jul 2018)
Introduction / Steve O'Connor -- 1. Leading change : knowledge for success / Ian Smith -- 2. Management fads and fashions and their impact on the LIS community / Bill Fisher -- 3. The Five Rules of Engagement for librarians : aux Ranganathan's laws of library science / Choy Fatt Cheong -- 4. Library management, disruption and consortia : an Australian example / Michael Robinson -- 5. No regrets ; just lessons : economic crisis is changing our life and the management of libraries / Petros A. Kostagiolas -- 6. Introducing agile principles and management to a library organization / Daniel Forsman -- 7. The role of professional associations in changing times / Susan Henczel -- 8. And the walls came tumbling down... The library profession confronts all-invasive new managerialism / Colin Storey -- 9. What is behind the meaning of disruption? Or, thinking of management strategies from the outside / Steve O'Connor
Keywords: Library administration; Library science / 21st century